Programming Languages with Applications to Biology and Security Essays Dedicated to Pierpaolo Degano on the Occasion of His 65th Birthday - Bodei, Chiara; Ferrari, Gianluigi; Priami, Corrado (Theoretical Computer Science and General Issues, 2015)
Programming Languages with Applications to Biology and Security  This Festschrift volume is published in honor of Pierpaolo Degano on the occasion of his 65th birthday and is the outcome of a colloquium held in Pisa, Italy, in June 2015. Pierpaolo Degano has worked on a large variety of topics including formal program semantics, concurrency theory, systems biology and security. The volume contains 22 refereed papers and one extended abstract, including personal memoirs and regular research papers by close collaborators and friends and a laudatio illustrating his distinguished career and his main scientific contributions. The papers deal with the main research topics explored by Pierpaolo Degano and those still under his investigation. .